1984
DOI: 10.1115/1.3239572
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Blade Design for Large Deflections: Part II—Annular Cascades

Abstract: A method of designing highly loaded blades to give a specified distribution of swirl is presented. The method is based on a newly developed, three-dimensional analysis. In the present application, the flow is assumed to be incompressible and inviscid (the annulus has constant hub and tip radii), and the blades are of negligible thickness. A simple free vortex swirl schedule is assumed. The flow velocity is divided into circumferentially averaged and periodic terms. The Clebsch formulation for the periodic velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 0 publications
1
51
0
1
Order By: Relevance
“…2 In the course of this work it was found that a converged solution is obtainable whenever the mean meridional velocity v,,, does not vanish and/or when the flow is not in the transonic regime. When v, vanishes, equation (29) for the blade shape indicates that d f / h + c o , which is not accounted for in the present work.…”
Section: Convergence and Consistencymentioning
confidence: 97%
“…2 In the course of this work it was found that a converged solution is obtainable whenever the mean meridional velocity v,,, does not vanish and/or when the flow is not in the transonic regime. When v, vanishes, equation (29) for the blade shape indicates that d f / h + c o , which is not accounted for in the present work.…”
Section: Convergence and Consistencymentioning
confidence: 97%
“…Tan et al (1984) proposed a theory of a large deflection blade design method. Zangeneh-Kazemi (1988) applied Tan et al (1984)'s method to their 3D flow designing of radial turbines.…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al (1984) proposed a theory of a large deflection blade design method. Zangeneh-Kazemi (1988) applied Tan et al (1984)'s method to their 3D flow designing of radial turbines. Yang et al (1993) and Tjokroaminata et al (1996) developed this method further and designed radial turbines with splitter blades.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly all inverse models are basically based on the inviscid assumption and some very useful simpliÿed design methods have been developed with e ort [3]. Concerning the inverse design of turbo-machinery, especially hydraulic machinery runner blades, a survey of published literature indicates that only a few real 3D inverse models, such as the Fourier series expansion singularity method [4,5], the pseudo-stream function method [6] and the inverse time marching method [7] have been reported. The pseudo-stream function method and the inverse time marching method are really an alteration of direct calculation and blade geometry modiÿcation.…”
Section: Introductionmentioning
confidence: 99%